2020
DOI: 10.1371/journal.pone.0230823
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural disparity in sociodemographic characteristics and sexual behaviors of HIV-positive adolescent girls and young women and their perspectives on their male sexual partners: A cross-sectional study in Zimbabwe

Abstract: We conducted a cross sectional survey in Zimbabwe to describe urban-rural disparity in socio-demographic characteristics and sexual behaviors of HIV-positive adolescent girls and young women (AGYW) and their male sexual partners. Between September and November 2016, we interviewed 360 sexually active HIV positive AGYW, aged 15-24 years attending ART and PMTCT clinics in urban and rural health facilities in Harare and Mazowe district respectively. HIV positive AGYW in rural areas as compared to those in urban a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…A study that assessed the prevalence and factors associated with HIV status disclosure among children and adolescents selected from urban and rural clinics across western Kenya reported a higher prevalence of disclosure among children at rural clinics than those at a large referral hospital in the urban area [8]. In contrast, a study done in Zimbabwe revealed that adolescent girls and young women in rural areas learned their HIVpositive status for the first time at an older age (median of 19 years), compared to those in urban areas (median of 16 years) [28]. Interestingly, in contrast to the results for the whole study population that female caregivers were less likely to disclose HIV status of their OVC, female caregivers of multiple OVCLHIV were more likely to disclose HIV status to all OVC living in the same household, compared to their male counterparts.…”
Section: Discussionmentioning
confidence: 89%
“…A study that assessed the prevalence and factors associated with HIV status disclosure among children and adolescents selected from urban and rural clinics across western Kenya reported a higher prevalence of disclosure among children at rural clinics than those at a large referral hospital in the urban area [8]. In contrast, a study done in Zimbabwe revealed that adolescent girls and young women in rural areas learned their HIVpositive status for the first time at an older age (median of 19 years), compared to those in urban areas (median of 16 years) [28]. Interestingly, in contrast to the results for the whole study population that female caregivers were less likely to disclose HIV status of their OVC, female caregivers of multiple OVCLHIV were more likely to disclose HIV status to all OVC living in the same household, compared to their male counterparts.…”
Section: Discussionmentioning
confidence: 89%
“…The acquisition of mobile phones in most of Zimbabwe's rural areas is increasing, making mobile phones the most feasible communication gadget for people in resource-constrained areas [17]. Also, many of Zimbabwe population (over 67%) lives in rural areas [58] and heavily depends on mobile phones for communication and making payments using mobile money platforms such as EcoCash, One-Money, MyCash and Tele-Cash because of cash shortages [59]. Owing to this proliferation, mobile phones especially short messaging service (SMS) could be utilized to promote and market IRS programme and campaigns in malaria hotspots area and high-risk population in Buhera rural district.…”
Section: Resultsmentioning
confidence: 99%
“…The ownership of mobile phones in most of Zimbabwe's rural areas is at the boom, making it the most feasible communication even in resource-constrained areas [33]. Also, many of Zimbabwe population (over 67%) lives in rural areas [57] and heavily depends on mobile phones for communication and making payments using mobile money platforms such as EcoCash, One-Money, MyCash and Tele-Cash because of cash shortages [58]. Owing to this proliferation, mobile phones especially short messaging service (SMS) could be utilized to promote and market IRS programme and campaigns in malaria hotspots area and high-risk population in Buhera rural district.…”
Section: Resultsmentioning
confidence: 99%